RESPON TANAMAN EDAMAME TERHADAP PEMBERIAN KOMPOS HIJAU DAN PGPR BAMBU DI TANAH ALUVIAL - Renaldi; Fadjar Rianto; Muhammad Pramulya (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2026)
Edamame, is a soybean originating from China, is widely cultivated as a vegetable plant and used as a snack. Edamame cultivation in West Kalimantan in alluvial soil has obstacles, namely the physical properties of hard and solid alluvial soil, soil biological properties that have poor microorganism activity. Efforts have been made to overcome these obstacles by using green compost and bamboo PGPR. The purpose of this study was to deteminethe interaction and effectiveness of green compost and bamboo PGPR in alluvial soil. The study was conducted in the city of Pontianak for ± 5 months. The study used a plot design divided into main factors consisting of 2 levels of bamboo PGPR, subplots consisting of 3 levels of green compost doses, namely k1 = 10 tons/ha, k2 = 20 tons/ha, k3 = 30 tons/ha so that 6 treatment combinations were produced that were repeated 4 times. The variables observed were the number of branches, dry weight, root volume, number of pods per plant, pod weight per plant. The results showed that there was no interaction between green compost and bamboo PGPR, the use of bamboo PGPR had an effect on the variables of root volume and pod weight, the percentage of seeded pods 2, the use of green compost had an effect on the percentage of edamame hollow pods in alluvial soil.